2019
DOI: 10.1186/s13104-019-4339-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of glycopeptide, aminoglycoside and macrolide resistance among clinical isolates of Enterococcus faecalis: a multicenter based study

Abstract: Objectives Enterococcus faecalis as part of the normal floras of human gastrointestinal and genitourinary tracts are an important cause of nosocomial infections. The present study aimed to investigate the prevalence of genes encoding antimicrobial resistance and genetic relatedness of clinical isolates of E. faecalis among Iranian hospitalized patients. Results Antibiotic susceptibility testing results indicated that 53 (22.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
4
11
2
1
Order By: Relevance
“…The resistance to vancomycin can be mediated by nine different types of van cluster genes (vanA -B, -C, -D, -E, -G, -L, -M, and -N) and we can distinguish them based on their physical location (encoded in the core genome or on a mobile genetic element); the level of resistance they confer; the specific glycopeptides to which they confer resistance (often distinguished operationally as providing resistance to both vancomycin and teicoplanin, or providing resistance to vancomycin but not teicoplanin); whether resistance is inducible or constitutively expressed; and the type of peptidoglycan precursor that is produced by their gene products. [10,11]. While the vanC gene characterizes the natural intrinsic resistance in some enterococci species, the others encode acquired resistance [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance to vancomycin can be mediated by nine different types of van cluster genes (vanA -B, -C, -D, -E, -G, -L, -M, and -N) and we can distinguish them based on their physical location (encoded in the core genome or on a mobile genetic element); the level of resistance they confer; the specific glycopeptides to which they confer resistance (often distinguished operationally as providing resistance to both vancomycin and teicoplanin, or providing resistance to vancomycin but not teicoplanin); whether resistance is inducible or constitutively expressed; and the type of peptidoglycan precursor that is produced by their gene products. [10,11]. While the vanC gene characterizes the natural intrinsic resistance in some enterococci species, the others encode acquired resistance [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, high-level resistance to aminoglycosides (HLGR) is usually acquired on a mobile element that encodes an aminoglycoside-modifying enzyme. Such an enzyme is usually the bifunctional aminoglycoside-modifying enzyme, AAC(6 )-Ie-APH(2 )-Ia, which is encoded by the aac(6 )-Ie-aph(2 )-Ia gene, reducing the effect of aminoglycosides except for streptomycin [9,11]. Furthermore, among gentamicin-resistant strains, three aminoglycoside resistance genes, i.e., aph(2 )-Ib, aph(2 )-Ic, and aph(2 )-Id, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…During 6 months of the study, a total of 53 VRE isolates were collected randomly with the possibility of true infections. Totally, of 53 confirmed VRE isolates, 56.6% and 43.4% isolates were obtained from female and male subjects, respectively 28. The most frequent isolates 35 (66%) were obtained from UTIs and followed that from respiratory infections and bloodstream infections.…”
Section: Resultsmentioning
confidence: 99%
“…Mamtora et al [11] reported that Enterococcus spp were highly susceptible to linezolid (96%), vancomycin (92%), and teicoplanin (93.3%) while being resistant to erythromycin and ciprofloxacin. Zallipour et al [12] reported the highest antibiotic resistance rates against tetracycline (93.5%), erythromycin (87%), and ciprofloxacin (80%) in E. faecalis isolates. They did not determine any resistance to fosfomycin or linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing prevalence of vancomycin resistant enterococci (VRE) has been reported in previous literature [16,17]. Zallipour et al [12] reported that 22.8% of 232 E. faecalis isolates were vancomycin resistant (MIC ≥ 256 μg/ml). Linezolid is the main treatment option in patients with VRE.…”
Section: Discussionmentioning
confidence: 99%